Morphological Characteristics of the Intestine of White Rats - Abduvaliev Fayzullo Zafarjon ugli (Research Journal of Trauma and Disability Studies, 2024)
In this article, the morphological structure of the wall of the duodenum is studied. The study of the morpho-functional indicators of the muscle fibers in the wall of the duodenum shows that they consist of a combined complex structure. The obtained results allow a deeper understanding of the mechanism of the occurrence of various changes in the muscular tissue of the duodenal wall. It was found that there is a layer of briquetting tissue with collagen fibers connecting the mucous and outer layers of the organ in the muscle fibers of the duodenal wall.